Little house on the prairie - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 2000)
Laura Ingalls travels with her family from the big woods of Wisconsin to the prairies of Kansas, where they build a house, meet neighboring Native Americans, and face the challenges of frontier life.
"First published in 1935; rev. ed. illustrated by Garth Williams published in 1953"--T.p. verso.
Book Links (A.L.A.).
Booklist.
Library Journal.
Book Links (A.L.A.), May 1996.
Booklist, April 2010.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Family life -- Fiction; Frontier and pioneer life -- Fiction; Historical fiction; Family life -- Fiction; Frontier and pioneer life -- Kansas -- Fiction; Historical fiction; Great Plains -- Fiction; Kansas -- History -- Fiction; Great Plains -- Fiction; Kansas -- History -- Fiction